Commitment and Quiet Quitting: A Qualitative Longitudinal Study - Harris, Lloyd C. (Human Resource Management, 2025)
ABSTRACTRecently scholars across a range of fields have noted the importance of the issue of quiet quitting in term of both pervasiveness and profundity of impact. Our study views quiet quitting as employees intentionally opting actively to manage their work/working lives to adhere to contracted duties/hours while avoiding voluntarily taking on additional responsibilities, tasks, or roles. To date, almost universally, existing studies assume that quiet quitting is a single, monolithic, homogenous phenomenon which relentlessly generates ‘bad’ outcomes for firms and ‘good’ outcomes for perpetrators. This current study addresses these important assumptions with a key aim of our research is to supply grounded evidence of the nature of quiet quitting and to examine the outcomes of such actions for perpetrators' longitudinally. To facilitate this, we adopt the concept of commitment as our conceptual lens for explicating how employees' quiet quitting is manifested and utilize a longitudinal, qualitative research design to gauge outcomes. After outlining existing research in the area, we detail our research design and methodology, before presenting the insights gained during data collection and analysis. Our paper concludes with a discussion of a series of contributions to both theory and practice.